Umrzeć z ciekawości. Portret rzymskiego naukowca - Piętka, Radosław (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
The paper provides an analysis of Pliny the Younger’s Vesuvian letter about the death of his uncle in the context of Roman beliefs concerning scientific activity. On these grounds some comparisons can be made between Pliny’s account and Roman didactic poetry.

It is common knowledge that Romans were far less involved than Greeks in the development of science. Nevertheless, there were some people in Roman society who were called ‘docti’ or even ‘doctissimi’. Nowadays we can call them ‘researchers’ or ‘scientists’, as well as “men of erudition”. The first step I had to take in my paper was therefore to examine the contexts in which these terms have been used in Latin. Furthermore, my essay tries to answer several other questions, e.g.: what is the exemplar of the Roman scientist? To what extent it is in agreement with the traditional set of Roman virtues? Fortunately, Roman literature preserved an interesting testimony concerning the life and, especially, noble death of the one of the most eminent Roman scientists, Pliny the Elder. Since according to this evidence his desire to observe the strange phenomenon during the eruption of Vesuvius led him finally to his death, so one could say he died of curiosity, I argue that curiosity and readiness to make the greatest sacrifices in the name of knowledge were among the most valued qualities attributed to those Roman researchers. In addition, I try to compare the evidence concerning Pliny the Elder with the ‘portrait of the scientist’ emerging from a Roman didactic epic (Lucretius’ De rerum natura, Vergil’s Georgics, and Manilius’ Astronomica in particular).
Dying of Curiosity. A Portrait of the Roman Scientist
Keywords: Pliny the Younger; Pliny the Elder; scientific curiosity; noble death